Prepubertal and Pubertal Canine Reproductive Studies: Conflicting Aspects - Gobello, María Cristina (2014)
Insufficient knowledge has been acquired regarding the prepubertal and pubertal periods of domestic canids. Until further information becomes available, a better standardization of the definitions, a careful and complete description of experimental variables and end points is necessary to diminish experimental bias in published trials. The aim of this report is therefore to discuss the definition of puberty and some of the most conflicting conditions influencing the pubertal transition (e.g. age and body weight and condition score among others) that, in turn, will be useful for the future design of reproductive studies on the domestic dog. Only trials that could be easily processed by a meta-analysis will contribute to an improvement of our general knowledge on the reproductive physiology of this particular species.